Penatalaksanaan Diabetes Mellitus pada Orang Dewasa - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
The aim of the diabetic treatment is to restore glucose intolerance to normal. There are abundant evidence that chronic hyperglycemia, from whatever cause, leads to chronic complications, such as angiopa thy, retinopathy, nephropathy and neuropathy. Prophylactic treatment should include good diabetic control and avoidance of other factors involving pathogenesis of atherosclerosis, e. obesity, smoking and hypertension. To achieve this aim, all diabetics, regardless of their age or the severity of their diabetes, must take an active role in managing their disease, and they must have adequate information about the importance of dietary management and must be instructed in suitable diet planning. Diet remains the cornerstone of the treatment of diabetes in adults. Meal-schedule, caloric intake and the composition of the diet must be a relative constant, against which is computed the necessary medication and the individual's exercise habits.Education of diabetic patients and their families should begin at the time of diagnosis. In long term diabetes education, the basic concepts of management should be reviewed together with patients during clinic visits at stated interval.Ketonuria usually means that insulin will be necessary.Key Word: diabetes mellitus — home glucose monitoring — dietary management — glocuse intolerance — diabetic education.